2013
DOI: 10.1007/s13201-013-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of chlorofluorocarbons (CFCs) to estimate the groundwater age at a headwater wetland in Ichikawa City, Chiba Prefecture, Japan

Abstract: To delineate the groundwater flow system in a basin, the groundwater age was estimated by analyzing chlorofluorocarbons (CFC-11, CFC-12 and CFC-113) in a typical headwater wetland in Ichikawa, Japan. Feasibility of groundwater dating by CFCs was assessed comprehensively based on the concentrations of NO 3-, SO 4 2-, Fe 2? and dissolved CH 4 in the groundwater, because the CFCs would be degraded under the reduction condition available in a wetland. It was found that the CFC-11 apparent age was much older than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…It was also obvious that ORP of groundwater trended decrease in the upward groundwater at all investigated sites, indicating that ORP of groundwater was decreasing along the groundwater flow direction. Furthermore, The pH and EC of groundwater were also trended decrease along the flow direction at most investigated sites, which was the same as the characteristics of NO 3 -and SO 4 2-in groundwater of the wetland (Han et al, 2014). It could be concluded that the characteristics of pH, ORP and EC of the groundwater were mainly affected by processes of reduction in the wetland, which was the biochemical purification.…”
Section: The Parameters Of Waters In the Wetlandsupporting
confidence: 59%
See 1 more Smart Citation
“…It was also obvious that ORP of groundwater trended decrease in the upward groundwater at all investigated sites, indicating that ORP of groundwater was decreasing along the groundwater flow direction. Furthermore, The pH and EC of groundwater were also trended decrease along the flow direction at most investigated sites, which was the same as the characteristics of NO 3 -and SO 4 2-in groundwater of the wetland (Han et al, 2014). It could be concluded that the characteristics of pH, ORP and EC of the groundwater were mainly affected by processes of reduction in the wetland, which was the biochemical purification.…”
Section: The Parameters Of Waters In the Wetlandsupporting
confidence: 59%
“…TDP concentrations of the spring water ranged from undetectable to 0.059 mg/L, and 2 samples (S7 and S16) exceeded the environmental standard (0.020 mg/L). Groundwater at different depth was observed in the middle of the wetland maintained under aerobic-, nitrate-, and sulfate-reducing conditions, and methanogenic conditions from 3 m to 1 m depth, respectively (Han et al, 2014). Wetlands are also used to treat municipal wastewater due to the reduction function (Yan et al, 2012).…”
Section: The Distribution Of Phosphorus In Groundwater and Spring Watermentioning
confidence: 99%
“…Certain ion ratios (Na + /K + , Na + /Ca 2+ ) in geothermal water, and even the content of a certain single component (Si) can indicate its circulation depth. Through the ratio of rubidium and strontium isotopes, the ambient petrophysical composition in the cycle of the thermal spring can be determined, and also the thermal spring circulation time can be calculated [33,34].…”
Section: Resultsmentioning
confidence: 99%